(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2013)
We have focused the research problem through an assessment of the applicability of the third pillar of the decisions of the Basel Committee 11 (market discipline) or not and its impact on both the adequacy of bank capital, supervisory oversight and banking risks and the statement weaknesses commitment banking institutions and which in turn lead to the stability of the financial system as a whole. . The research is important statement on the importance of big capital in the banking business and the attributes of a role in the absorption of losses suffered by the bank, which reflects the willingness of Iraqi banks banking safety through their applicability to those decisions. The objective of this research to study the effect of market discipline in each of the axis of capital adequacy, the hub of supervisory oversight and the axis of banking risks in a sample object-is likely through the study of the results of responses Alm_nin (Angels accounting) in the light of the application questionnaire exploratory consisted of (69) paragraph as final After checking the degree of sincerity and persistence to collect information distributed on four main themes (market discipline, capital adequacy, supervisory control, and banking risks) included a number paragraphs each (22, 23, 13, 11), respectively, in addition to the presence of some of the questions demographic characteristics of respondents and the related subject of the study, study came to a number of conclusions classified according to the results of the respondents in the statistical analysis, we recall the most important thing in which he said the following- Achieved results of the analysis linear correlation of hand and analyze the results of linear regression on the other hand the importance of the relationship with positive trend between the impact axis (market discipline) in function of both (Axis Capital adequacy axis supervisory oversight, and the axis of banking risks) and the significance of moral high, which confirming the validity of the assumptions the subject of the test and to achieve the objectives for which they came searching- Is evidenced by extracting per worker in the factor analysis in a manner basic vehicle level axes surveyed not to differences in their relative importance is generally in light derived from the values ​​of the covariance which formed the nature of the essence of the phenomenon researched and that sure which check if style one of the variance common as a result of overlapping themes together also been named Group Abstract light saturation ratios achieved when each axis of axes surveyed by a factor (the moral components of the third pillar of the Basel -11 (market discipline) came for the first time (according to the best of our knowledge), the study also came with a number of recommendations. credit - Total deposits at private banks in particular, by reducing the amounts of (premiums) insurance required by the private banks with insurance companies contracting with them. - Offers the potential human, and material to the supervisory authorities to enable them to commit their affiliated banks using third pillar of Basel 11, and follow-up of compliance with disclosure requirements to be high capacity, and provide them with modern techniques